gamma-(S)-Guanidinylmethyl-Modified Triplex-Forming Peptide Nucleic Acids Increase Hoogsteen-Face Affinity for a MicroRNA and Enhance Cellular Uptake - Tähtinen V; Verhassel A; Tuomela J; Virta P (WILEY-V C H VERLAG GMBH, 2022)
gamma-Modified (i.e., (S)-aminomethyl, (S)-acetamidomethyl, (R)-4-(hydroxymethyl)triazol-1-ylmethyl, and (S)-guanidinylmethyl) triplex-forming peptide nucleic acids (TFPNAs) were synthesized and the effect of the backbone modifications on the binding to a miR-215 model was studied. Among the modifications, an appropriate pattern of three gamma-(S)-guanidinylmethyl modifications increased the affinity and Hoogsteen-face selectivity for the miR-215 model without ternary (PNA)(2)/RNA complex formation. Moreover, the gamma-(S)-guanidinylmethyl groups were observed to facilitate internalization of the TFPNAs into living PC-3 prostate cancer cells.